2009
DOI: 10.1901/jaba.2009.42-355
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Excessive Straightening and Destructive Behavior in an Adolescent Diagnosed With Autism

Abstract: Repetitive behaviors such as excessive straightening are commonly observed among individuals with autism. Attempts to prevent these behaviors may increase the likelihood of other problem behaviors. The present study was designed to assess and treat the excessive straightening and associated destructive behaviors of a 16-year-old boy who had been diagnosed with autism and moderate mental retardation. Following a series of functional analyses, an intervention that incorporated functional communication, extinctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 10 publications
2
44
0
Order By: Relevance
“…By identifying relevant consequences, their associated discriminative stimuli, and establishing operations that control OCD symptoms and alternate behavior, interventions may be developed to reduce those symptoms and increase functionally related alternate behavior (Sturmey 1996(Sturmey , 2007(Sturmey , 2009. Three studies identified consequences maintaining compulsive behavior in ASD (Hsu and Ho 2009;Kuhn et al 2009). …”
Section: Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…By identifying relevant consequences, their associated discriminative stimuli, and establishing operations that control OCD symptoms and alternate behavior, interventions may be developed to reduce those symptoms and increase functionally related alternate behavior (Sturmey 1996(Sturmey , 2007(Sturmey , 2009. Three studies identified consequences maintaining compulsive behavior in ASD (Hsu and Ho 2009;Kuhn et al 2009). …”
Section: Assessmentmentioning
confidence: 99%
“…Kuhn et al (2009) conducted a functional analysis to determine the reinforcers maintaining aggressive behavior related to being blocked from throwing away nontrash items in a 16-year-old boy with autism. Aggression was followed by five contingent consequences presented in a multi-element design: toy play, social attention, tangible, demand, and ignore (Iwata et al 1982).…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations